An exploratory study on design elements in restaurant interiors that contribute to intimate conversations among married couples in Metro Manila - Lopez, Wryanne Jasmine P.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The purpose of this study is to explore how specific design elements in restaurant interiors may influence interpersonal communication between couples that in turn, may affect the level of shared intimacy. Fifteen Filipino couples residing in Metro Manila with children living at home and have been married for 5-25 years were selected to participate in this study. Through a qualitative research design, survey questionnaires distributed to 15 couples included an inquiry into their existing interpersonal communication patterns and mood boards that sought to measure their behavioral responses in line with intimate communication with their spouse. An adaptation of the Mehrabian-Russell Stimulus Response Model (1974) was applied to the framework of this study. The variables that were added to this framework included marital quality and satisfaction as mediators and restaurant design elements as the stimulus. The findings of the study revealed that intimate interpersonal communication was influenced by the couples perception on their surroundings given the context of a restaurant setting. To an extent, both design factors and ambient factors contributed to how the couples responded to sharing intimate conversations with their spouse. In addition, it was presented that the restaurant design elements that contributed much to intimate conversations between the couples were furniture and accessories for the design factors, and lighting, scent, and room temperature for the ambient factors. According to the self-reported data, an increase in appeal leads to an increase in tendency to approach, thereby resulting in more frequent intimate conversations between the spouses. In conclusion, the study was able to discover that the presence of appealing design elements in restaurants contributed to marital interpersonal communication.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Restaurants -- Decoration -- Philippines